(untitled) (Comillas Journal of International Relations, 2016)
There is no doubting the ambivalence of Churchill’s attitude to France as a British Francophile but also as a British patriot. Much depended on whether he perceived the interests of Britain and those of France as coinciding, as was fortunately the case for most of the period, and the article examines the ups and downs of his relations with the French through his long career, beginning with his first stay in Paris in 1883 and ending with his obvious enjoyment of the French Riviera after his withdrawal from world affairs in 1955. In between, the way he managed to surmount the major crises in Anglo-French relations, notably after June 1940, is discussed in the light of what must definitely be seen as an indefectible life-long attachment in spite of all the difficulties.